2022
DOI: 10.1159/000522111
|View full text |Cite
|
Sign up to set email alerts
|

Oncological Outcomes after Pulmonary Metastasectomy for Head and Neck Squamous-Cell Carcinoma and Adenoid Cystic Carcinoma

Abstract: <b><i>Introduction:</i></b> Pulmonary metastatic head and neck cancer has a poor prognosis. Pulmonary metastasectomy has been performed but only in carefully selected patients. The aim of this study was to examine the clinical characteristics and oncological follow-up of patients who underwent pulmonary metastasectomy. <b><i>Methods:</i></b> Data of 54 patients with squamous-cell carcinoma (SCC) or adenoid cystic carcinoma (ACC) who underwent metastasectomy betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…By 8 years, the DFS dropped to 0% in this cohort, demonstrating difficulty in achieving a permanent oncologic cure through PM alone. While these percentages are substantially lower than the other studies analyzed here, it is important to note that the authors only reported DFS and not OS, and it is likely that many of these patients survived significant periods of time after the appearance of their second recurrence, given the often slowly progressive nature of ACC [ 135 ].…”
Section: Local Therapy For Oligometastatic Lung Diseasementioning
confidence: 79%
See 1 more Smart Citation
“…By 8 years, the DFS dropped to 0% in this cohort, demonstrating difficulty in achieving a permanent oncologic cure through PM alone. While these percentages are substantially lower than the other studies analyzed here, it is important to note that the authors only reported DFS and not OS, and it is likely that many of these patients survived significant periods of time after the appearance of their second recurrence, given the often slowly progressive nature of ACC [ 135 ].…”
Section: Local Therapy For Oligometastatic Lung Diseasementioning
confidence: 79%
“…Most recently, a 2022 study which included 18 ACC patients reported 1-, 3-, and 5-year post-PM disease-free survival (DFS) rates of 88.9%, 38.9%, and 32.4%, respectively [ 135 ]. By 8 years, the DFS dropped to 0% in this cohort, demonstrating difficulty in achieving a permanent oncologic cure through PM alone.…”
Section: Local Therapy For Oligometastatic Lung Diseasementioning
confidence: 99%